ANALISIS NILAI BUDAYA DALAM SEDEKAH BUMI DI DESA TEGOWANU WETAN, KECAMATAN TEGOWANU KABUPATEN GROBOGAN - Tyas Pitaloka; Wasino; Arghita Aricindy; Tri Astuti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze the culture values contained in the earth alms tradition in Tegowanu Village, Tegowany District, Grobogan Regency. This research uses a descriptive qualitative method, employing data collection techniques such as interviews and library research (i.e. reading and taking notes from books or journals). Tegowanu has a sedekah bumi tradition that is held once a year in the “Bulan Apit” (in the Javanese calendar) and the month of Dzulqo’dah (in the Hijri calendar). The execution of this sedekah bumi tradition consists of: bathing (penjamasan) sacred heirloom objects, ambengan (communal meal), and a shadow puppetry performance. The findings showa that the sedekah bumi tradition actually holds deeply embedded cultural values, such as: local wisdom, mutual cooperation (gotong royong), tolerance, togetherness among residents, and social care.